2019
DOI: 10.4067/s0718-221x2019005000413
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical characteristics of impregnated white Jabon wood ( Anthocephalus cadamba ) using merbau extractives and selected polymerised merbau extractives

Abstract: This paper presents results of a study on the mechanical characteristics of impregnated Jabon wood (Anthocephalus cadamba) using Merbau extractives (ME) and two types of polymerised Merbau extractives (PME), i.e PME22 and PME33. A set of tests on hardness, shear, modulus of elasticity (MOE) and modulus of rupture (MOR) was conducted according to the relevant standards. Two types qualitative analysis by means of FTIR spectra and XRD analysis were carried out to explore relationship between the mechanical charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…This shortcoming can be solved by thermal treatment [ 25 , 26 ]. Merbau extractives have potential as an impregnating material for low-quality timber to improve its properties [ 27 , 28 ]. The effect of higher temperatures on selected fire safety features of tropical wood shows that the thermal treatment of merbau and meranti wood significantly increased its flammability and accelerated its combustion [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…This shortcoming can be solved by thermal treatment [ 25 , 26 ]. Merbau extractives have potential as an impregnating material for low-quality timber to improve its properties [ 27 , 28 ]. The effect of higher temperatures on selected fire safety features of tropical wood shows that the thermal treatment of merbau and meranti wood significantly increased its flammability and accelerated its combustion [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Boric acid and borax increased the hardness of varnished wood surface (Ors et al 2007). Malik and Ozarska (2019) reported that the density and hardness of white jabon wood ( Anthocephallus cadamba ) increased after impregnation with polymerized merbau extractives.…”
Section: Resultsmentioning
confidence: 99%
“…Rahayu et al (2014) and Darmawan et al (2013) related to the point of differentiation (demarcation) between juvenile and mature wood in sengon and jabon; Fajriani et al (2013) about variations in the properties of the wood in the radial direction, Widiyanto and Siarudin (2016) related to the shaving properties of the wood as raw material for frames; and Nugroho et al (2011) about the physical and mechanical properties of the wood. Chemical modification and impregnation on the jabon wood could improve quality and resistance to termite attacks (Hadi et al 2013(Hadi et al , 2015Komariah et al 2015;Hadiyane et al 2018;Lestari et al 2018;Arsyad et al 2019;Hadi et al 2019;Malik and Ozarska. 2019;Prihartini et al 2020;Hadi et al 2021;Malik et al 2022).…”
Section: Introductionmentioning
confidence: 99%